Is Suicide the Unforgivable Sin? Understanding Suicide, Stigma, and Salvation through Two Christian Perspectives - Potter, John (Religions, 2021)
Is suicide the unforgivable sin? Most Western arguments against suicide stem from Christian arguments. Christianity has a long-standing position that suicide is morally wrong. However, on the issue of suicide and salvation, Christianity is divided. Debate, discussion, and interpretation through the centuries have led to two different positions. This result has divided the Christian community in multiple ways. These beliefs have likely impacted the level of stigma associated with suicide losses, suicide attempts, and suicide survivors within Christianity. The stigma of suicide can be lethal if it is not properly addressed. Stigma can easily push people away from caring communities of support and from God. This paper examines the two predominate Christian theological positions on suicide and highlights areas where stigma has hindered help, support, and care. Lowering the negative effects of suicidal stigma is a foundational piece of the solution for communities of faith to engage people at risk of suicide.